Attitudes and perceptions of medical doctors towards the local health system: a questionnaire survey in Ecuador - Esteban Ortiz-Prado; Marta Fors; Aquiles R. Henriquez-Trujillo; Gabriel H. Cevallos-Sierra; Alejandra Barreto-Grimaldos; Katherine Simbaña-Rivera; Lenin Gomez-Barreno; Eduardo Vasconez; Alex Lister (BMC, 2019)
Abstract Background Health systems worldwide rely on health professionals to deliver services and provide framework structures. Considering their opinions about their work environment, the public policies that regulate their work and the deficiencies of the health care system are key aspects of the governance within the system. The aim of this study was to assess the perceptions of Ecuadorian physicians about several aspects of the performance of the health delivery and monitoring systems locally. Methods A cross-sectional survey was performed in a group of physicians in Ecuador during 2017 using a self-selection sampling strategy. The participants were contacted by telephone, direct email or in person and asked to complete the online survey which contained 47 questions. Results A total of 607 full responses were received from physicians, where 68.6% of those had graduated within the last 17 years. 46.4% of respondents were medical specialists, 23.1% general practitioners, 10.0% rural health practitioners, 9.5% sub-specialists, 5.9% were formally enrolled in a specialty program and 5.1% were researchers or administrative physicians. Data analysis of the answers showed that approximately 62% of physician respondents in the study found their current workload at the time of the survey was unmanageable, the most common complaints about the Public Health system in the study being the amount of daily paperwork (78.4%), followed by a perceived lack of vision of the health authorities (60.1%) and the resource limitations within the public hospitals (53.5%). Additionally, 71.8% of respondents referred to limitations of the National Essential Medicines chart- especially on the availability of some drugs- and 57.5% of the respondents reported concerns about the quality of medicines available for treatment. Conclusions The data provide basic inputs for health authorities regarding the functioning of the health system in Ecuador. Health professionals' concerns can be a valuable resource for monitoring and improving health system performance: however, there is a perceived sense of disconnection between the governance or management and the service delivery arms of the healthcare system in Ecuador. Whilst not representative of the entirety of the population of doctors, the study does give insight into where improvements to the health system might be made.